2016
DOI: 10.1093/icvts/ivw152
|View full text |Cite
|
Sign up to set email alerts
|

Functional and postoperative outcomes after preoperative exercise training in patients with lung cancer: a systematic review and meta-analysis

Abstract: Lung cancer is the leading cause of cancer-related death worldwide. For early stages of the disease, lung resection surgery remains the best treatment with curative intent, but significant morbidity is associated, especially among patients with poor pulmonary function and cardiorespiratory fitness. In those cases, the implementation of a preoperative exercise-based intervention could optimize patient's functional status before surgery and improve postoperative outcomes and enhance recovery. The aim of this sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
92
1
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 183 publications
(102 citation statements)
references
References 69 publications
3
92
1
6
Order By: Relevance
“…Early ambulation and oral nutrition can better maintain muscle function and promote the recovery of gastrointestinal peristalsis . Early respiratory function training can promote the recovery of lung function . On the premise of ensuring safety, early extubation can relief postoperative pain and mental disturbances, also encourage patients to get out of bed earlier .…”
Section: Discussionmentioning
confidence: 99%
“…Early ambulation and oral nutrition can better maintain muscle function and promote the recovery of gastrointestinal peristalsis . Early respiratory function training can promote the recovery of lung function . On the premise of ensuring safety, early extubation can relief postoperative pain and mental disturbances, also encourage patients to get out of bed earlier .…”
Section: Discussionmentioning
confidence: 99%
“…Although it is well understood that PR may improve preoperative pulmonary function and functional status, its effect on reducing perioperative pulmonary complications has not been clearly demonstrated . A few studies have shown a significant benefit of PR on clinical outcomes in patients with NSCLC, but these studies also included many non‐COPD patients . No study has shown that PR reduces postoperative pulmonary complications specifically in patients with COPD and NSCLC.…”
Section: Introductionmentioning
confidence: 99%
“…Preoperative exercise has been shown to improve cardiorespiratory function [13, 62]. It is likely to confer change in other vascular beds, including the mesenteric arterial system.…”
Section: Resultsmentioning
confidence: 99%